Pengaruh Ruang Terbuka Hijau dalam Mengatasi Bencana Abrasi Berdasarkan Persepsi Masyarakat di Desa Bedono - Septya Unzillarachma; Mussadun Mussadun (Jurusan Perencanaan Wilayah dan Kota, 2020)
Bedono Village is located in the north coast of Java, which is part of DemakRegency. Bedono village is often affected by disasters such as abrasion and rob. This abrasion disaster has long been occurring in Bedono Village which has an impact in the form of damaged roads, loss of human settlements, destruction of mangrove forests and reduced marine ecosystems in the Bedono. It is suspected that the abrasion disaster was caused by the lack of green open space in the village of Bedono. Specifically the green open space in question is mangrove forest. So the importance of this research to examine the effect of green open space in the form of mangrove plants in overcoming the abrasion disaster according to community perception. This study uses a quantitative ordinal linear regression method, which is used to assess the effect of green open space in overcoming abrasion. The results obtained from this study are shown that with a 95% confidence level the green open space variable that has an effect on overcoming this abrasion disaster is a plant type (X1) with a significant value of 0,16. Then the soil texture variable (X2) with a significant value of 0,15. And plant spacing variables (X5) with a significant value of 0,15; 0,003; 0,000. The significant value is <0,05, so that the green open space variables that influence in overcoming this abrasion disaster are plant type,soil texture and planting distance.